2000
DOI: 10.1063/1.481655
|View full text |Cite
|
Sign up to set email alerts
|

Cavity ringdown spectroscopy of the linear carbon chains HC7H, HC9H, HC11H, and HC13H

Abstract: Optical bands from the Σu−3←X Σg−3 transition of the linear carbon chains HC7H, HC9H, HC11H, and HC13H have been measured in the gas phase by cavity ringdown spectroscopy. The bands exhibit well resolved P and R branches, which for HC7H are partially rotationally resolved. Comparisons between observed and simulated spectra indicate broadening in excess of that expected from the laser linewidth and Doppler width, suggesting rapid radiationless transitions in roughly 0.1–0.01 ns, a time scale consistent with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 22 publications
3
69
0
1
Order By: Relevance
“…To check whether there are equivalent H-atoms in this carrier, a C 2 H 2 /C 2 D 2 1:1 mixture in He has been used as an expansion gas, but this only results in a very broad absorption feature covering the whole region where results are found for a pure C 2 H 2 and a pure C 2 D 2 expansion. It is impossible to conclude anything about the actual number of equivalent H-atoms in the carrier by determining the number of bands that show up, as could be demonstrated for HC 6 H + or HC 7 H (Sinclair et al 1999;Ball et al 2000a;Khoroshev et al 2004). Also the use of another precursor (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To check whether there are equivalent H-atoms in this carrier, a C 2 H 2 /C 2 D 2 1:1 mixture in He has been used as an expansion gas, but this only results in a very broad absorption feature covering the whole region where results are found for a pure C 2 H 2 and a pure C 2 D 2 expansion. It is impossible to conclude anything about the actual number of equivalent H-atoms in the carrier by determining the number of bands that show up, as could be demonstrated for HC 6 H + or HC 7 H (Sinclair et al 1999;Ball et al 2000a;Khoroshev et al 2004). Also the use of another precursor (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the electronic transitions of a series of PAH-cations do not match the listed DIBs (Salama et al 1996(Salama et al , 1999Bréchignac & Pino 1999;Ruiterkamp et al 2002). Similarly, systematic laboratory studies of electronic spectra of carbon chain radicals have not resulted in positive identifications either (Motylewski et al 2000;Ball et al 2000a;Jochnowitz & Maier 2008), even though it is known from combined radioastronomical and Fourier transform microwave (FTMW) studies that many of such species are present in dense clouds (Thaddeus & McCarthy 2001). Only C 3 has been recorded unambiguously in diffuse interstellar clouds (Maier et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Respective absorption spectra for chains containing up to 19 carbon atoms have been measured in neon matrices (n = 2 − 7, 9) and in the gas phase by resonant two-color two-photon ionization (R2C2PI; n = 3 − 6, 9) and cavity ring down spectroscopy (CRDS; n = 3 − 6). [11][12][13][14] Attempts to measure the 1 3 Σ − u ← X 3 Σ − g transition for the smallest members HC 3 H and HC 5 H in the gas phase failed so far. Whereas the two C 3 H 2 isomers with C 2v symmetry, which are more stable, were studied, [15][16][17][18][19] arguments were given for the non-observation of the electronic transition of HC 5 H, including low oscillator strength and unfavorable production conditions.…”
Section: Introductionmentioning
confidence: 99%
“…14 Particularly interesting are the n = odd members of the HC n H series, because they are open-shell and their lowest energy electronic transition falls in the visible and near infrared. HC 2n+1 H have been studied in the optical domain by direct absorption in neon 15 and nitrogen 16 matrices and in the gas phase by cavity ring-down 17,18 and resonance enhanced multiphoton ionization methods. 19 They were also studied by ab initio methods.…”
Section: Introductionmentioning
confidence: 99%